“Growing Greener, Better Future”, Analisis Komunikasi Lingkungan Pupuk Kalimantan Timur di Desa Wisata Malahing Menuju Green Sustainable Development - Molekandella Boer, Kheyene; Ainun Nimatu Rohma; Annisa Wahyuni Arsyad (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2025)
This study aims to analyze the implementation of environmental communication by the fertilizer industry in supporting the development of a sustainable tourism village in Malahing Village, Bontang, East Kalimantan, which is under the auspices of the East Kalimantan Fertilizer Company (PKT). This research method used a qualitative approach. Data were collected through interviews with key informants from PKT, the village government, and local community groups, as well as direct observation of environmental management in the village. The results indicate that PKT has implemented various environmental communication policies, such as the development of environmentally friendly infrastructure (landfills, sanitation, and waste transportation vehicles) and community outreach on the importance of environmental cleanliness and sustainability. However, the main challenges faced are low levels of active community participation in waste management and environmental awareness, which still needs to be improved. The role of Local heroes, such as the neighborhood association (RT) head and the head of the tourism awareness group, is crucial in effectively conveying environmental communication messages. This study concludes that the environmental communication implemented in Malahing Village needs to be strengthened by directly involving more community members in environmental management to ensure the sustainability of this tourism village. Keywords: Environmental Communication, Local Hero, Sustainability, Tourism Village, Waste Management. .